OZONE THERAPY IN THE TREATMENT OF PATIENTS WITH ECZEMA - Abdurakhmanov Akhrorbek Avazbek ugli (Scholar Express Journals, 2024)
The article describes ozone therapy techniques used to treat eczema and psoriasis as an adjuvant anti-inflammatory and reparative agent. Parenteral and external use of an oxygen-ozone gas mixture (the so-called medical ozone) is used both in the form of monotherapy and in complex treatment. The proposed systemic and external methods allow differentiated prescribing of ozone therapy depending on the nature and duration of the disease, the activity of the inflammatory process and the presence of concomitant diseases
Keywords: ozone therapy; treatment; psoriasis